Financial literacy externalities - Michael Chaliasos; Thomas Jansson; Yigitcan Karabulut (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2018)
This paper uses unique administrative data and a quasi-field experiment of exogenous allocation in Sweden to estimate medium- and longer-run effects on financial behavior from exposure to financially literate neighbors. It contributes evidence of causal impact of exposure and of a social multiplier of financial knowledge, but also of unfavorable distributional aspects of externalities. Exposure promotes saving in private retirement accounts and stockholding, especially when neighbors have economics or business education, but only for educated households and when interaction possibilities are substantial.Findings point to transfer of knowledge rather than mere imitation or effects through labor, education, or mobility channels.
urn:nbn:de:hebis:30:3-488021
Keywords: G11; E21; D14; F22; I28; 330; household finance; financial literacy; social interactions; refugees